Desirability of Outcome Ranking for the Management of Antimicrobial Therapy (DOOR MAT) Reveals Improvements in the Treatment of Bloodstream Infections Caused by Escherichia coli and Klebsiella pneumoniae in Patients from the Veterans Health Administration. (12th May 2021) - Perez, Federico; Colindres, Roberto Viau; Wilson, Brigid M; Saade, Elie; Jump, Robin L P; Banerjee, Ritu; Patel, Robin; Evans, Scott R; Bonomo, Robert A
Abstract: Background: Reductions in the use of broad-spectrum antibiotics is a cornerstone of antimicrobial stewardship. We aim to demonstrate use of the Desirability of Outcome Ranking Approach for the Management of Antimicrobial Therapy (DOOR MAT) to evaluate the treatment of Escherichia coli and Klebsiella pneumoniae bloodstream infections in patients from the Veterans Health Administration (VHA) across a decade. Methods: Using electronic records, we determined empiric and definitive antibiotic treatments, clinical characteristics, and 30-day mortality of patients with monomicrobial E. coli and K. pneumoniae bloodstream infections hospitalized in VHA medical centers from 2009 to 2018. Focusing on patients treated with parenteral β-lactams and with available antibiotic susceptibility testing results, we applied a range of DOOR MAT scores that reflect the desirability of antibiotic choices according to spectrum and activity against individual isolates. We report trends in resistance and desirability of empiric and definitive antibiotic treatments. Results: During the 10-year period analyzed, resistance to expanded-spectrum cephalosporins and fluoroquinolones increased in E. coli but not in K. pneumoniae, while resistance to carbapenems and piperacillin-tazobactam remained unchanged. In 6451 cases analyzed, we observed improvements in DOOR MAT scores consistent with deescalation. Improvement in desirability of definitive treatment compared with empiric treatment occurred in 26% of cases, increasing from 16% in 2009 to 34% in 2018. Reductions in overtreatment were sustained and without negative impact on survival. Conclusions: DOOR MAT provides a framework to assess antibiotic treatment of E. coli and K. pneumoniae bloodstream infections and can be a useful metric in antimicrobial stewardship. Abstract : The Desirability of Outcome Ranking for the Management of Antimicrobial Therapy (DOOR MAT) quantified improvements in antibiotic treatment of Escherichia coli and Klebsiella pneumoniae bloodstream infections at the Veterans Health Administration and is a useful tool for evaluating antimicrobial stewardship.